1998
DOI: 10.1021/ie980022i
|View full text |Cite
|
Sign up to set email alerts
|

Two- and Three-Phase Flows in Bubble Columns:  Numerical Predictions and Measurements

Abstract: Multiphase flows are widely encountered in many chemical reactor processes. Multiphase flow reactors in the form of bubble columns are used in many industrial applications such as hydrogenation of heavy oils, fermentation processes, Fischer-Tropsch reactors, etc. Past work in the modeling of these flows was based on empirical correlations. Even though these correlations fit the data well, they were applicable for narrow ranges of experimental parameters. Moreover, detailed information regarding the local flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
1
3
0
1
Order By: Relevance
“…The reason why the heat transfer appeared to only affect temperature is that the energy equation was not coupled with material or momentum equations. If this equation is only used for only pressure and velocity profiles, an energy equation is not necessary; these results reflect those of many researchers. , …”
Section: Trend Analysissupporting
confidence: 78%
“…The reason why the heat transfer appeared to only affect temperature is that the energy equation was not coupled with material or momentum equations. If this equation is only used for only pressure and velocity profiles, an energy equation is not necessary; these results reflect those of many researchers. , …”
Section: Trend Analysissupporting
confidence: 78%
“…The first reason is reasonable but cannot account for all the change. The second reason is better justified by Lindsay et al (1995) and has also been cited in other gas-liquid-so lid cocurrent flows (Mitra-Majumdar et al, 1998). Janse et al (1999) also reported that when the superficial liquid velocity increased, gas holdup increased, but this column was a counter-current flow column, where the liquid flowed downward in the column.…”
Section: Effect Of Superficial Gas Velocitymentioning
confidence: 79%
“…Comparison between experimental and simulated solid-liquid and gas-liquid-solid flow are difficult to achieve, as experimental data are provided on either velocity profiles [12], phase fraction profiles [8][13], [20] or contour plots [8][9][10][11] [21][22][23]. It is apparent from [1] that the prediction of the gas phase fraction requires further refinement with the inclusion of coalescence and disruption models [24].…”
Section: Resultsmentioning
confidence: 99%
“…Solid phase transport in bubbly flows has been characterised through different numerical prediction methods [7][8][9][10][11][12][13]. Many models were implemented in the prediction of solid phase fractions, from a fluidised solid phase to suspended solids being agitated by discrete bubbles or by a pseudo-continuous gas phase [7][8][9][10][11][12][13]. It must be noted that neither of the solid phase schemes allow for particle collisions and interactions as described by Gidaspow [7][8] and Fan [10][11].…”
Section: Introductionmentioning
confidence: 99%